Solid electrolyte and battery

By covering the polydopamine layer on the surface of the electrolyte particles and using the multi-copolymer structural units, the problems of poor interface contact and poor dispersion in the composite polymer solid electrolyte are solved, and solid electrolyte with high ionic conductivity and mechanical strength are achieved, improving the The battery cycle performance.

CN119419339AActive Publication Date: 2025-02-11SHENZHEN HAODYNE TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510015917.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

In the composite polymer solid electrolyte, the interface contact between the polymer and the inorganic ceramic particles is poor, and the dispersion of the inorganic ceramic particles leads to low ionic conductivity and uneven mechanical strength.

Method used

By covering the polydopamine layer on the surface of the electrolyte particles, negatively charged modified electrolyte particles are formed to avoid agglomeration, and binding and flexibility are improved through cyano groups, organic acids and acrylate structural units in the multi-copolymer.

Benefits of technology

The uniform dispersion of the modified electrolyte is achieved, the ionic conductivity and mechanical strength of the solid electrolyte are improved, and the circulation capacity retention rate of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a solid electrolyte and a battery. The solid electrolyte comprises a multipolymer and a modified electrolyte, wherein the multipolymer comprises a cyano structural unit, an organic acid structural unit and an acrylate structural unit; the modified electrolyte comprises electrolyte particles and polydopamine located on the surfaces of the electrolyte particles. According to the solid electrolyte provided by the invention, the surfaces of the electrolyte particles are coated with the polydopamine coating layer, so that the modified electrolyte has negative electricity and is prevented from being agglomerated in the multi-component copolymer, and hydrogen bonds are formed between N, O and reactive hydrogen in the polydopamine coating layer and the multi-component copolymer; and the binding force between the multipolymer and the modified electrolyte is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a solid electrolyte and a battery. Background Art

[0002] Since their commercialization, lithium-ion batteries have been widely used in portable electronic devices and electric vehicles. Currently, a series of problems caused by liquid electrolytes, such as electrode dissolution, electrode side reactions, lithium dendrite growth and poor thermal stability, have made lithium-ion batteries with higher energy density, longer cycle life and higher safety an urgent need in the current market. Solid-state batteries use solid electrolytes with a wide electrochemical stability window, high modulus and high thermal stability, which have the potential to match high-capacity electrode materials, inhibit lithium dendrite growth and improve safety. At the same time, all-solid-state batteries use metal lithium negative electrodes to achieve higher energy density. Therefore, solid-state lithium-ion battery technology has good development prospects.

[0003] The realization of excellent electrochemical performance of all-solid-state lithium-ion batteries requires its core - solid electrolyte with high ionic conductivity and excellent electrolyte / electrode interface contact. Solid polymer electrolytes have good flexibility and excellent contact with the positive electrode, but their ionic conductivity is low and their mechanical strength is insufficient to inhibit the growth of lithium dendrites. At present, by adding inorganic ceramic fillers to solid polymer electrolytes, high ionic conductivity (10 -4 S / cm), and has the advantages of polymer flexibility and good interface contact. However, the interface contact between the polymer and the inorganic ceramic particles in the composite polymer electrolyte is poor, and the dispersion of the inorganic ceramic particles in the polymer is poor, resulting in generally low ionic conductivity of the composite solid electrolyte, and uneven distribution of the ionic conductivity and strength of the electrolyte, which ultimately affects the performance of the assembled battery. Summary of the invention

[0004] Aiming at the technical problems in the prior art that the interface contact between the polymer and the inorganic ceramic particles in the composite polymer solid electrolyte is poor and the dispersibility of the inorganic ceramic particles is poor, the present invention provides a solid electrolyte and a battery.

[0005] In order to solve the above technical problems, on the one hand, the present invention provides a solid electrolyte, wherein the solid electrolyte comprises a multi-polymer and a modified electrolyte, wherein the multi-polymer comprises a cyano structural unit, an organic acid structural unit and an acrylate structural unit; The modified electrolyte includes electrolyte particles and polydopamine located on the surface of the electrolyte particles.

[0006] Preferably, the mass ratio of the multipolymer to the modified electrolyte is (20-60): (40-80).

[0007] Preferably, the mass ratio of the cyano structural unit, the organic acid structural unit and the acrylate structural unit is (50-70): (10-30): (20-40).

[0008] Preferably, the organic acid structural unit is a sulfonic acid structural unit; the sulfonic acid structural unit is selected from at least one of C2-C14 olefin sulfonic acid structural units, styrene sulfonic acid structural units, styrene sulfonic acid alkyl derivative structural units, C5-C18 sulfohydroxyalkyl acrylate structural units, C5-C18 sulfohydroxyalkyl methacrylate structural units, C5-C18 sulfoalkyl methacrylamide structural units, and C3-C18 alkyl allyl sulfosuccinic acid structural units.

[0009] Preferably, the cyano structural unit is selected from one or more of an acrylonitrile structural unit, a styrene nitrile structural unit, a methacrylonitrile structural unit, an ethyl acrylonitrile structural unit, a propyl acrylonitrile structural unit, an ethyl 2-cyano-3-ethoxyacrylate structural unit, an ethyl cyanoacrylate structural unit, a tetrakis(4-cyanophenyl)ethylene structural unit, a 2-cyano-5-norbornene structural unit, and a benzylmalononitrile structural unit; The acrylic acid ester structural unit is selected from the group consisting of methyl acrylate structural unit, ethyl acrylate structural unit, n-propyl acrylate structural unit, isopropyl acrylate structural unit, n-butyl acrylate structural unit, isobutyl acrylate structural unit, tert-butyl acrylate structural unit, n-pentyl acrylate structural unit, isopentyl acrylate structural unit, n-hexyl acrylate structural unit, n-octyl acrylate structural unit, isooctyl acrylate structural unit, isobornyl acrylate structural unit, phenoxyethyl acrylate structural unit, dicyclopentenyl acrylate structural unit, cyclohexyl acrylate structural unit, benzyl acrylate structural unit, methyl methacrylate structural unit, ethyl methacrylate structural unit, n-propyl methacrylate structural unit, isopropyl methacrylate structural unit, n-butyl methacrylate structural unit, isobutyl methacrylate structural unit, tert-butyl methacrylate structural unit, n-pentyl methacrylate structural unit, methyl methacrylate structural unit, At least one of isopentyl methacrylate structural units, n-hexyl methacrylate structural units, isooctyl methacrylate structural units, isobornyl methacrylate structural units, phenoxyethyl methacrylate structural units, dicyclopentenyl methacrylate structural units, cyclohexyl methacrylate structural units, benzyl methacrylate structural units, ethylene glycol diacrylate structural units, ethylene glycol dimethacrylate structural units, ethoxylated ethylene glycol diacrylate structural units, ethoxylated ethylene glycol dimethacrylate structural units, allyl methacrylate structural units, diallyl phthalate structural units, diallyl adipate structural units, trimethylolpropane triacrylate structural units, trimethylolpropane trimethacrylate structural units, pentaerythritol diacrylate structural units, pentaerythritol dimethacrylate structural units, pentaerythritol triacrylate structural units, and pentaerythritol trimethacrylate structural units.

[0010] Preferably, the mass ratio of the polydopamine to the electrolyte particles is (5-30): (70-95).

[0011] Preferably, the polydopamine is coated on the surface of the electrolyte particles to form a polydopamine coating layer, and the thickness of the polydopamine coating layer is 5 to 30 nm.

[0012] Preferably, the volume average particle size D50 of the electrolyte particles is 0.3-3 μm.

[0013] Preferably, the electrolyte particles include one or more of LLTO, LLZO, and LAGP.

[0014] On the other hand, the present application provides a battery, comprising a negative electrode, a positive electrode and the solid electrolyte as described in any one of the above items.

[0015] The solid electrolyte provided by the present application forms a coating layer on the surface of the electrolyte particles by using polydopamine and utilizing its adhesion. Its structure makes the electrolyte particles negatively charged, and the strong electrostatic repulsion makes the electrolyte particles coated with polydopamine show extremely strong stability, avoiding agglomeration when the modified electrolyte particles are compounded with the multi-polymer, so that the modified electrolyte is evenly dispersed in the multi-polymer, ensuring the uniformity and consistency of the strength of the solid electrolyte, and obtaining a composite polymer solid electrolyte. The N, O and active hydrogen in the polydopamine coating form hydrogen bonds with the multi-polymer, improving the binding force between the multi-polymer and the modified electrolyte, and ensuring the bonding strength between the electrolyte particles and the polymer. The chain segments of polydopamine are flexible, improving the interface contact with the multi-polymer, and reducing the interface resistance. The flexibility of the multi-polymer is improved by introducing an acrylic ester structural unit. The oxidation resistance of the multi-polymer is improved by introducing a cyano structural unit into the multi-polymer, and the high-voltage positive electrode material is adapted. By introducing organic acid structural units into the multipolymer, the main chain of the multipolymer has electronegative groups, which provides a stable transmission channel for lithium ions. Under the action of the electric field, lithium ions migrate between adjacent organic acid radical groups on the chain segments of the multipolymer through a transition transmission mechanism, thereby enhancing ion transmission and facilitating the improvement of the ionic conductivity of the solid electrolyte. DETAILED DESCRIPTION

[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0017] An embodiment of the present application provides a solid electrolyte, the solid electrolyte comprising a multi-polymer and a modified electrolyte, the multi-polymer comprising a cyano structural unit, an organic acid structural unit and an acrylate structural unit; The modified electrolyte includes electrolyte particles and polydopamine located on the surface of the electrolyte particles.

[0018] The solid electrolyte provided in this embodiment makes the modified electrolyte negatively charged by coating the surface of the electrolyte particles with a polydopamine coating layer, avoids the modified electrolyte from agglomerating in the multi-polymer, and makes the modified electrolyte uniformly dispersed in the multi-polymer, thereby ensuring the uniformity and consistency of the strength of the solid electrolyte. The N, O and active hydrogen in the polydopamine coating layer form hydrogen bonds with the multi-polymer, thereby improving the binding force between the multi-polymer and the modified electrolyte. The chain segment of polydopamine has flexibility, which improves the interface contact with the multi-polymer. The flexibility of the multi-polymer is improved by introducing an acrylic ester structural unit. The oxidation resistance of the multi-polymer is improved by introducing a cyano structural unit into the multi-polymer, and the high-voltage positive electrode material is adapted. By introducing an organic acid structural unit into the multi-polymer, the main chain of the multi-polymer has an electronegative group, which provides a stable transmission channel for lithium ions. Under the action of the electric field, the lithium ions migrate between the adjacent organic acid radical groups on the chain segment of the multi-polymer through the mechanism of transition transmission, thereby strengthening the ion transmission and facilitating the improvement of the ionic conductivity of the solid electrolyte. Furthermore, the solid electrolyte of this embodiment can have a high ion conductivity without adding lithium salt.

[0019] In some embodiments, the mass ratio of the multi-polymer to the modified electrolyte is (20-60): (40-80). By controlling the mass ratio of the multi-polymer to the modified electrolyte, the ionic conductivity and mechanical strength of the solid electrolyte are improved.

[0020] Specifically, the mass ratio of the modified electrolyte to the multi-polymer includes, but is not limited to, 40:60, 50:50, 65:35, 70:30, 75:25 or 80:20.

[0021] In some embodiments, the mass ratio of the cyano structural unit, the organic acid structural unit and the acrylate structural unit is (50-70): (10-30): (20-40). By controlling the mass ratio of each structural unit, the oxidation resistance and flexibility of the multi-polymer can be regulated.

[0022] Specifically, the mass ratio of the cyano structural unit, the organic acid structural unit and the acrylate structural unit includes but is not limited to 50:20:30, 60:20:20, 60:10:30, 65:15:20, 70:10:20. In the present invention, the mass ratio of the above structural units is based on the mass ratio between the raw material monomers corresponding to the structural units when participating in the polymerization to obtain the multi-component copolymer.

[0023] In some embodiments, the cyano structural unit is a structural unit obtained by polymerization of a cyano-containing monomer, and the cyano structural unit is selected from one or more of an acrylonitrile structural unit, a styrene nitrile structural unit, a methacrylonitrile structural unit, an ethyl acrylonitrile structural unit, a propyl acrylonitrile structural unit, a 2-cyano-3-ethoxyethyl acrylate structural unit, an ethyl cyanoacrylate structural unit, a tetrakis(4-cyanophenyl)ethylene structural unit, a 2-cyano-5-norbornene structural unit, and a benzylmalononitrile structural unit.

[0024] In some embodiments, the organic acid structural unit is preferably a sulfonic acid structural unit, specifically a structural unit obtained by polymerization of a monomer containing a sulfonic acid group, and the sulfonic acid structural unit is selected from C2-C14 olefin sulfonic acid structural units (e.g., vinyl sulfonic acid structural units, methyl allyl sulfonic acid structural units, allyl sulfonic acid structural units, methyl vinyl sulfonic acid structural units), styrene sulfonic acid structural units, styrene sulfonic acid alkyl derivative structural units (the alkyl group may have 2-24 carbon atoms, such as α-methyl styrene sulfonic acid structural units), C5-C18 acrylic acid sulfohydroxyalkyl ester structural units, C5-C18 methacrylic acid sulfohydroxyalkyl ester structural units (e.g., methacrylate sulfopropyl ester structural units, 2-hydroxy-3- At least one of methacryloyloxypropylsulfonic acid structural unit, 2-methacryloyloxyethanesulfonic acid structural unit, 3-methacryloyloxy-2-hydroxypropanesulfonic acid structural unit), C5-C18 sulfoalkylmethacrylamide structural unit (e.g., 2-methacrylamide-2,2-dimethylethanesulfonic acid structural unit, 2-methacrylamide-2-methylpropanesulfonic acid structural unit, 2-acrylamide-2-methylpropanesulfonic acid structural unit, 3-methacrylamide-2-hydroxypropanesulfonic acid structural unit), C3-C18 alkylallylsulfosuccinic acid structural unit (e.g., propylallylsulfosuccinic acid structural unit, butylallylsulfosuccinic acid structural unit, 2-ethylhexyl-allylsulfosuccinic acid structural unit). More preferably, the sulfonic acid structural unit is a 2-acrylamide-2-methylpropanesulfonic acid structural unit.

[0025] In some embodiments, the acrylic acid ester structural unit is a structural unit obtained by polymerization containing acrylic acid ester monomers, and the acrylic acid ester structural unit is selected from methyl acrylate structural unit, ethyl acrylate structural unit, n-propyl acrylate structural unit, isopropyl acrylate structural unit, n-butyl acrylate structural unit, isobutyl acrylate structural unit, tert-butyl acrylate structural unit, n-pentyl acrylate structural unit, isopentyl acrylate structural unit, n-hexyl acrylate structural unit, n-octyl acrylate structural unit, isooctyl acrylate structural unit, isobornyl acrylate structural unit, phenoxyethyl acrylate structural unit, dicyclopentenyl acrylate structural unit, cyclohexyl acrylate structural unit, benzyl acrylate structural unit, methyl methacrylate structural unit, ethyl methacrylate structural unit, n-propyl methacrylate structural unit, isopropyl methacrylate structural unit, n-butyl methacrylate structural unit, isobutyl methacrylate structural unit, tert-butyl methacrylate structural unit The present invention comprises at least one of a structural unit, a n-pentyl methacrylate structural unit, an isopentyl methacrylate structural unit, a n-hexyl methacrylate structural unit, an isooctyl methacrylate structural unit, an isobornyl methacrylate structural unit, a phenoxyethyl methacrylate structural unit, a dicyclopentenyl methacrylate structural unit, a cyclohexyl methacrylate structural unit, a benzyl methacrylate structural unit, an ethylene glycol diacrylate structural unit, an ethylene glycol dimethacrylate structural unit, an ethoxylated ethylene glycol diacrylate structural unit, an ethoxylated ethylene glycol dimethacrylate structural unit, an allyl methacrylate structural unit, a diallyl phthalate structural unit, a diallyl adipate structural unit, a trimethylolpropane triacrylate structural unit, a trimethylolpropane trimethacrylate structural unit, a pentaerythritol diacrylate structural unit, a pentaerythritol dimethacrylate structural unit, a pentaerythritol triacrylate structural unit, and a pentaerythritol trimethacrylate structural unit.

[0026] Preferably, the polydopamine is coated on the surface of the electrolyte particles to form a polydopamine coating layer.

[0027] In some embodiments, the mass ratio of the polydopamine to the electrolyte particles is (5-30): (70-95). By controlling the mass ratio of polydopamine to the electrolyte particles, the electrolyte particles are ensured to be completely coated, and the final particle size of the modified electrolyte is controlled.

[0028] Specifically, the mass ratio of polydopamine to electrolyte particles includes, but is not limited to, 5:95, 10:90, 20:80, 15:85, 25:75 or 30:70.

[0029] In some embodiments, the thickness of the polydopamine coating layer is 5-30 nm. The thickness of the polydopamine coating layer on the surface of the electrolyte particles can be measured by scanning electron microscopy (SEM).

[0030] In some embodiments, the volume average particle size D50 of the electrolyte particles is 0.3-3 μm.

[0031] In some embodiments, the electrolyte particles include one or more of LLTO, LLZO, and LAGP. The above electrolyte particles can be directly purchased from commercial sources. When purchasing, electrolyte particles with a required volume average particle size D50 can be directly selected.

[0032] Specifically, the preparation method of the solid electrolyte comprises the following steps: The cyano monomer, organic acid monomer and acrylate monomer are mixed, and an initiator is added to prepare a multi-component copolymer by emulsion polymerization. The above specific operation is known to those skilled in the art and will not be described in detail in the present invention.

[0033] Polydopamine (PDA) is used to coat the electrolyte particles by ball milling using a high-energy ball milling method to obtain a modified electrolyte.

[0034] It should be noted that if polydopamine (PDA) is first mixed with a multipolymer and then the mixture is mixed with electrolyte particles, polydopamine cannot be attached to the surface of the electrolyte particles and further form the above-mentioned coating layer, and the purpose of the present invention cannot be achieved.

[0035] The multi-polymer and the modified electrolyte are mixed in a certain ratio, and a mixed slurry of a composite electrolyte is obtained after dispersion. The composite solid electrolyte slurry is coated on a release film by a coating casting method, and a solid electrolyte is obtained after drying.

[0036] Among them, polydopamine has polar groups, has wettability and super strong adhesion to inorganic electrolyte particles, and can coat inorganic electrolyte particles to form "nanocoating", whose structure makes the modified electrolyte negatively charged, and the strong electrostatic repulsion makes the electrolyte particles wrapped by PDA show strong stability. The connection between the benzene ring and the functional group on the PDA main chain makes the PDA main chain show a certain flexibility.

[0037] An embodiment of the present application provides a battery, comprising a negative electrode, a positive electrode, and the solid electrolyte as described in any of the above embodiments.

[0038] The present invention is further described below by way of examples.

[0039] The solid electrolyte and battery disclosed in the present invention are specifically described.

[0040] Example 1 Solid electrolyte Acrylonitrile, 2-acrylamido-2-methylpropanesulfonic acid and ethyl acrylate were mixed in a mass ratio of 60:15:25, and then a multi-component copolymer was prepared by an emulsion polymerization method.

[0041] LLTO was ball-milled and coated with polydopamine (PDA) using a high-energy ball milling method to obtain a modified electrolyte.

[0042] The multipolymer and the modified electrolyte are mixed in a mass ratio of 20:80, and a mixed slurry of a composite electrolyte is obtained after dispersion. The composite solid electrolyte slurry is coated on a release film by a coating casting method, and a solid electrolyte is obtained after drying.

[0043] Preparation of negative electrode A lithium sheet is selected as the negative electrode.

[0044] Preparation of positive electrode The positive electrode active material high nickel ternary (NCM811), conductive carbon black, and positive electrode binder are mixed in a mass ratio of 90:3:7, and NMP is added to prepare positive electrode slurry. The positive electrode slurry is coated on aluminum foil and dried to obtain a positive electrode sheet.

[0045] Battery preparation Assemble the negative electrode sheet, positive electrode sheet and solid electrolyte into a battery.

[0046] Embodiments 2 to 19 Most of the steps of Examples 2 to 19 are the same as those of Example 1, except that the formulations in Tables 1 and 2 are used.

[0047] Comparative Examples 1 to 4 Most of the steps of Comparative Examples 1 to 4 are the same as those of Example 1, except that the formulations in Table 1 and Table 2 are used.

[0048] Table 1

[0049] Table 2

[0050] Electrical performance test: The solid electrolytes and batteries prepared in the above examples and comparative examples were subjected to the following tests.

[0051] 1. Ionic conductivity: The positive and negative electrodes in the preparation method of the all-solid-state lithium-ion battery were replaced with two pieces of stainless steel foil as blocking electrodes, and the AC impedance test was performed using the Shanghai Chenhua electrochemical workstation, with the frequency range set to 0.1-1MHz and the amplitude set to 10mV, and the ionic conductivity test was performed at room temperature (30°C); 2. Mechanical properties test: The mechanical properties of the solid electrolyte are characterized by stress tensile test. Before the test, the environment of the instrument is dehumidified and the ambient temperature is controlled at 25°C. The solid electrolyte to be tested is cut into a size of 50 mm long and 10 mm wide. The stretching speed is set to 6 mm / min and the clamping distance is 20 mm. 3. Capacity retention rate test: The all-solid-state lithium-ion battery is charged and discharged at a constant current of 60°C and a current density of 0.2C within the range of 2.8 to 4.0V, and the initial discharge specific capacity and the discharge specific capacity after 500 cycles are tested, and the capacity retention rate is calculated.

[0052] The test results are shown in Table 3 below.

[0053] Table 3

[0054] It can be seen from the above test results that the solid electrolyte provided by the present invention has excellent ionic conductivity and tensile strength, and can effectively improve the cycle capacity retention rate of the solid-state battery.

[0055] It can be seen from the test results of Example 1 and Comparative Example 4 that by coating the polydopamine layer on the surface of the electrolyte particles, the ionic conductivity and tensile strength of the solid electrolyte are significantly higher than those of Comparative Example 4, and the cycle life of the battery is also significantly improved, further proving that the polydopamine coating layer and the multi-polymer have a good synergistic effect.

[0056] It can be seen from the test results of Example 1 and Comparative Examples 1 to 3 that the multi-polymer contains cyano structural units, organic acid structural units and acrylate structural units at the same time, which makes the solid electrolyte have better ionic conductivity and tensile strength.

[0057] It can be seen from the test results of Examples 1 to 13 that when the mass ratio of the cyano structural unit, the organic acid structural unit and the acrylate structural unit in the multi-polymer is in the range of (50-70): (10-30): (20-40), the solid electrolyte has good ionic conductivity and tensile strength.

[0058] It can be seen from the test results of Examples 16 to 19 that when the mass ratio of the multi-polymer to the modified electrolyte is in the range of (20 to 60): (40 to 80), the solid electrolyte has good ionic conductivity and tensile strength.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid electrolyte, characterized in that The solid electrolyte comprises a multi-polymer and a modified electrolyte, wherein the multi-polymer comprises a cyano structural unit, an organic acid structural unit and an acrylate structural unit; The modified electrolyte includes electrolyte particles and polydopamine located on the surface of the electrolyte particles.

2. The solid electrolyte according to claim 1, characterized in that The mass ratio of the multi-polymer to the modified electrolyte is (20-60): (40-80).

3. The solid electrolyte according to claim 1, characterized in that The mass ratio of the cyano structural unit, the organic acid structural unit and the acrylate structural unit is (50-70): (10-30): (20-40).

4. The solid electrolyte according to claim 1, characterized in that The organic acid structural unit is a sulfonic acid structural unit; The sulfonic acid structural units are selected from at least one of C2-C14 olefin sulfonic acid structural units, styrene sulfonic acid structural units, styrene sulfonic acid alkyl derivative structural units, C5-C18 sulfohydroxyalkyl acrylate structural units, C5-C18 sulfohydroxyalkyl methacrylate structural units, C5-C18 sulfoalkyl methacrylamide structural units, and C3-C18 alkyl allyl sulfosuccinic acid structural units.

5. The solid electrolyte according to claim 1, characterized in that The cyano structural unit is selected from one or more of an acrylonitrile structural unit, a styrene nitrile structural unit, a methacrylonitrile structural unit, an ethyl acrylonitrile structural unit, a propyl acrylonitrile structural unit, an ethyl 2-cyano-3-ethoxyacrylate structural unit, an ethyl cyanoacrylate structural unit, a tetrakis(4-cyanophenyl)ethylene structural unit, a 2-cyano-5-norbornene structural unit, and a benzylmalononitrile structural unit; The acrylic acid ester structural unit is selected from the group consisting of methyl acrylate structural unit, ethyl acrylate structural unit, n-propyl acrylate structural unit, isopropyl acrylate structural unit, n-butyl acrylate structural unit, isobutyl acrylate structural unit, tert-butyl acrylate structural unit, n-pentyl acrylate structural unit, isopentyl acrylate structural unit, n-hexyl acrylate structural unit, n-octyl acrylate structural unit, isooctyl acrylate structural unit, isobornyl acrylate structural unit, phenoxyethyl acrylate structural unit, dicyclopentenyl acrylate structural unit, cyclohexyl acrylate structural unit, benzyl acrylate structural unit, methyl methacrylate structural unit, ethyl methacrylate structural unit, n-propyl methacrylate structural unit, isopropyl methacrylate structural unit, n-butyl methacrylate structural unit, isobutyl methacrylate structural unit, tert-butyl methacrylate structural unit, n-pentyl methacrylate structural unit, methyl methacrylate structural unit, At least one of isopentyl methacrylate structural units, n-hexyl methacrylate structural units, isooctyl methacrylate structural units, isobornyl methacrylate structural units, phenoxyethyl methacrylate structural units, dicyclopentenyl methacrylate structural units, cyclohexyl methacrylate structural units, benzyl methacrylate structural units, ethylene glycol diacrylate structural units, ethylene glycol dimethacrylate structural units, ethoxylated ethylene glycol diacrylate structural units, ethoxylated ethylene glycol dimethacrylate structural units, allyl methacrylate structural units, diallyl phthalate structural units, diallyl adipate structural units, trimethylolpropane triacrylate structural units, trimethylolpropane trimethacrylate structural units, pentaerythritol diacrylate structural units, pentaerythritol dimethacrylate structural units, pentaerythritol triacrylate structural units, and pentaerythritol trimethacrylate structural units.

6. The solid electrolyte according to claim 1, characterized in that The mass ratio of the polydopamine to the electrolyte particles is (5-30): (70-95).

7. The solid electrolyte according to claim 1, characterized in that The polydopamine is coated on the surface of the electrolyte particles to form a polydopamine coating layer, and the thickness of the polydopamine coating layer is 5-30 nm.

8. The solid electrolyte according to claim 1, characterized in that The volume average particle size D50 of the electrolyte particles is 0.3-3 μm.

9. The solid electrolyte according to claim 1, characterized in that The electrolyte particles include one or more of LLTO, LLZO, and LAGP.

10. A battery, characterized in that: The method comprises a negative electrode, a positive electrode and a solid electrolyte as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Separator for lithium ion secondary battery, and lithium ion secondary battery

    CN102334215A

  • Preparation method of high-performance polymer / inorganic ceramic composite solid electrolyte

    CN114927749A

  • Composite electrolyte with stable gradient distribution structure, battery and preparation method

    CN115441048A

  • Composite solid electrolyte diaphragm, preparation method thereof and lithium ion battery

    CN116345069A

  • Solid electrolyte composition for lithium metal secondary battery and preparation method

    CN116914239A